User Experience (UX) on Search Semantic Modeling Using Iterative Process Flow Method - Irfan Santiko; Arief Hidayat (Universitas Amikom Purwokerto, 2022)
On a website application platform, the search feature is one of the most important things in digging up the information in it. In addition, when compared to the search feature on search engines, searching for information on certain sites will produce more specific information. Semantic Web is a technique that allows content on the Web to be more understandable by computers. The Semantic Web itself is often equated with Web 3.0. These Semantic Web technologies include RDF, OWL, and SPARQL. In this paper the author tries to solve a research object problem in an elementary school in terms of finding diploma information for elementary school students. With the Semantic Web technology, it can make it easier to store and search E-Archive data. If archiving still uses the manual method for storing archives so as to avoid the constraints of difficulty finding archives, errors in storage, damage, to the threat of fire. With the application of semantic Web technology, it can be a solution to quickly store and search diploma archive data in a computerized Diploma E-Archive.